2019
DOI: 10.1002/cpt.1701
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen‐Induced Liver Damage in Hepatic Steatosis

Abstract: One of the most used painkillers is acetaminophen (APAP), which is safe at the right dose. However, several studies have described populations susceptible to APAP-induced liver damage, mainly in livers with steatosis. Thus, clinicians should consider the presence of obesity and other chronic liver diseases like nonalcoholic fatty liver disease (NAFLD) when indicating treatment with APAP. Liver damage from this drug is generated through its metabolite N-acetyl-pbenzoquinone imine, which is detoxified with gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 95 publications
3
14
0
1
Order By: Relevance
“…These models disclosed higher cytotoxicity of APAP [257], troglitazone [236] and a mixture of benzo[a]pyrene and J o u r n a l P r e -p r o o f ethanol [240,247] in NAFLD cells compared with the non-steatotic cells. Regarding APAP toxicity [257], these in vitro investigations confirmed previous studies carried out in obese mice and humans with NAFLD [228,232,244]. Furthermore, mechanistic investigations showed that higher CYP2E1 activity in lipid-loaded HepaRG cells was, at least in part, responsible for higher APAP cytotoxicity [257].…”
Section: Implications Of Dili In Clinical Contextssupporting
confidence: 83%
See 1 more Smart Citation
“…These models disclosed higher cytotoxicity of APAP [257], troglitazone [236] and a mixture of benzo[a]pyrene and J o u r n a l P r e -p r o o f ethanol [240,247] in NAFLD cells compared with the non-steatotic cells. Regarding APAP toxicity [257], these in vitro investigations confirmed previous studies carried out in obese mice and humans with NAFLD [228,232,244]. Furthermore, mechanistic investigations showed that higher CYP2E1 activity in lipid-loaded HepaRG cells was, at least in part, responsible for higher APAP cytotoxicity [257].…”
Section: Implications Of Dili In Clinical Contextssupporting
confidence: 83%
“…This paradigm implies two possible scenarios. First, drugs such as APAP (in the context of overdose), halothane and isoflurane may cause more severe and/or more frequent ALF in individuals with NAFLD [228,232]. Second, pharmaceuticals such as irinotecan, methotrexate and tamoxifen seem to be more hepatotoxic in obese patients than in lean individuals by triggering the transition from steatosis to NASH, and/or worsening pre-existing steatosis, necroinflammation and fibrosis [55,233,234].…”
Section: Implications Of Dili In Clinical Contextsmentioning
confidence: 99%
“…In addition, these models unveiled increased cytotoxicity of acetaminophen [ 50 ], troglitazone [ 52 ] and a mixture of benzo[a]pyrene and ethanol [ 51 , 53 ] in MAFLD cells compared with non-steatotic cells. Regarding acetaminophen [ 50 ], these in vitro investigations confirmed previous studies carried out in obese mice with MAFLD [ 44 , 45 , 57 ]. In contrast, we found that ritonavir was less cytotoxic in MAFLD cells compared with the non-steatotic cells [ 52 ].…”
Section: How To Test This Hypothesis?supporting
confidence: 85%
“…DILI in MAFLD seems to occur as two distinct clinical situations [ 38 , 39 , 43 ]. First, some drugs such as acetaminophen and some antibiotics may cause more severe and/or more frequent acute liver injury ( Table 2 ) [ [43] , [44] , [45] ]. Regarding, acetaminophen, it should be pointed out that its hepatotoxicity is mainly observed after overdose but some cases of liver injury (sometimes severe) may also occur with recommended therapeutic dosing [ 39 , 46 , 47 ].…”
Section: Hypothesis: Are Covid-19 Patients With Pre-existing Mafld Atmentioning
confidence: 99%
“…Several studies reported that its administration is more dangerous in patients already suffering from NAFLD, NASH or obesity. APAP-induced liver damage is related to the CYP3A4 and CYP2E1-mediated generation of its metabolite N-acetyl-p-benzoquinone imine (NAPQI), which is detoxified by glutathione (GSH) [ 208 ]. In already compromised hepatocytes, as they are in NAFLD or NASH, GSH stores are poor because of the increased activity of CYP450, in particular CYP2E1, which is post-transductionally upregulated by insulin.…”
Section: Drugs Inducing Hepatic Steatosismentioning
confidence: 99%